The Beauty of the syllabic form in the poetic image - The River of Sorrows poem model - Ahmed, Nermin Ghaleb (Journal of Humanities & Social Sciences, 2019)
The syllable voice is the cornerstone in phonetics; the verses in poetry are segmented first into segments, and then a distinction is made between short syllables and long syllables, at that point these syllables are categorized according to certain rhythmic bases in larger units called "measures". In the poem under study the poet positions us since the beginning in an atmosphere of hidden semantic meanings throughout the use of open syllables (CV-CVV), and there is no doubt that these syllables have significance to expose sharp emotions hiding inside the self in its conflict with others or with itself, whereas the closed syllable (CVC) portrays the poet’s agitation and the overlapped devotions. The number of the open syllables is as twice as the closed syllables the matter that fits the poem atmosphere and makes the rhythm fast and influential.